1999
DOI: 10.1095/biolreprod60.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Pulsatile Secretion of Luteinizing Hormone and Follicle-Stimulating Hormone during Different Phases of the Estrous Cycle and Anestrus in Beagle Bitches

Abstract: The 6-h secretory profiles of LH and FSH and the possible concordance between the episodic release of LH and FSH were studied in 6 beagle bitches during early, mid-, and late anestrus and during the follicular and luteal phases of the estrous cycle. Plasma samples were obtained at 10-min intervals via jugular venipuncture. In all stages of anestrus and in the luteal phase, FSH and LH secretion was pulsatile. All FSH pulses coincided with LH pulses. However, the mean duration of the FSH pulse (115 min) was sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
46
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 34 publications
8
46
0
3
Order By: Relevance
“…In agreement with the findings of others, GnRH administration elicited a distinct release of LH [4,[7][8][9][10] and FSH [10]. The course of the GnRH-induced surges in FSH and LH in the anestrous bitches was comparable to what has been reported previously for spontaneous FSH and LH pulses in anestrous bitches [1]. The GnRH-induced plasma LH increments above the pre-GnRH levels were much greater than the corresponding FSH increments.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In agreement with the findings of others, GnRH administration elicited a distinct release of LH [4,[7][8][9][10] and FSH [10]. The course of the GnRH-induced surges in FSH and LH in the anestrous bitches was comparable to what has been reported previously for spontaneous FSH and LH pulses in anestrous bitches [1]. The GnRH-induced plasma LH increments above the pre-GnRH levels were much greater than the corresponding FSH increments.…”
Section: Discussionsupporting
confidence: 91%
“…Although all pre-GnRH plasma LH concentrations were higher in OVX dogs than in sexually intact dogs, measurement of circulating LH concentration in a single sample has limited potential for distinguishing between OVX and sexually intact bitches. Taking into account the strong pulsatile nature of LH release [1,13], an overlap in the plasma LH concentration between larger groups of intact and OVX bitches may be expected. Indeed, in the current study GnRH-induced LH increments in the intact bitches overlapped pre-GnRH plasma LH concentrations in the OVX bitches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In bitches, administration of dopamine agonists during both the luteal phase and anoestrus results in shortening of the interoestrous interval in the bitch [23][24][25][26]. It has been shown that this dopamine agonist-induced shortening of the interoestrous interval in the bitch is associated with an increase in circulating FSH concentration [27].…”
Section: Introductionmentioning
confidence: 99%
“…In dogs, follicle stimulating hormone (FSH) pulses appear to occur www.journals.elsevierhealth.com/periodicals/the Theriogenology 66 (2006) [1419][1420][1421][1422] concomitantly with LH pulses in all stages of the estrous cycle and anestrus [3]. The pre-ovulatory LH-surge is also associated with a surge in FSH secretion [4].…”
Section: Introductionmentioning
confidence: 99%